Makna Syifa’ dalam Alquran dan Relevansinya dengan Sains Modern - Arifin, Muhammad Patri (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2020)
This article is a library research which aims to reveal the meaning of syifa’ in the Qur’an and its relevance to modern science. Syifa’ theme is an important theme that deserves elaborated to reveal the purpose of its mention which is then linked to the development of science. Its use in the form of nakirah (general) is considered by many as the universality of its content, which then triggers various opinions among commentators regarding the scope of its meaning, characteristics, goals and functions, whether in the form of the Qur’an, verses or something that is considered to be healing. By using thematic methods and a historical-sociological approach to the term of syifa’ in the Qur’an, this article comes to the finding that syifa’ has relevance to modern science which includes aspects of spiritual therapy, aspects of medical therapy and psychotherapy, as well as aspects of holistic therapy.